2016
DOI: 10.1073/pnas.1604658114
|View full text |Cite
|
Sign up to set email alerts
|

Common and heritable components of white matter microstructure predict cognitive function at 1 and 2 y

Abstract: Previous studies indicate that the microstructure of individual white matter (WM) tracts is related to cognitive function. More recent studies indicate that the microstructure of individual tracts is highly correlated and that a property common across WM is related to overall cognitive function in adults. However, little is known about whether these common WM properties exist in early childhood development or how they are related to cognitive development. In this study, we used diffusion tensor imaging (DTI) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 45 publications
(72 reference statements)
14
45
0
Order By: Relevance
“…34,35 ; similarly, myelination increases more gradually after the second year 36,37 . The diffusion properties of white-matter tracts are highly correlated with each other at birth, but this correlation decreases with development as tracts mature and differentiate 38 .…”
Section: Structural Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 ; similarly, myelination increases more gradually after the second year 36,37 . The diffusion properties of white-matter tracts are highly correlated with each other at birth, but this correlation decreases with development as tracts mature and differentiate 38 .…”
Section: Structural Developmentmentioning
confidence: 99%
“…Factors that describe common variation of FA, AD or RD across groups of white matter tracts are weakly related to cognitive development in an age-specific way; for example, a common factor of AD across 12 white matter tracts at birth is associated with cognitive development at age 1 year. 38 .…”
Section: Predicting Risk and Cognitive Functionmentioning
confidence: 99%
“…Accordingly, experiments in mice exposed to diesel particles pre‐ and neo‐natally showed a reduction in the area of the corpus callosum (the largest white matter tract) and dilatation of the ventricles (indicating white matter damage). The area of the corpus callosum during weeks 28‐32 of gestation has been reported to predict post‐natal neurobehavioural impairment in children . Similarly, white matter tracts and microstructure at birth are suggested to predict general cognition in infancy .…”
Section: Are Children More Vulnerable?mentioning
confidence: 99%
“…There is consistent evidence that impaired placental function disrupts foetal neurodevelopment in animals and neurobehavioural development in children. Altered placental function is associated with the development of the corpus callosum in the foetal brain and with brain function in neonates and brain connectivity at one year of age . Experimentally reducing oxygen and nutrients during the last third of gestation in rabbits could result in poorer neurobehavioural performance and network diffusion early in life …”
Section: What Are the Potential Mechanisms Underlying The Effects Of mentioning
confidence: 99%
“…Similarly, WM volumes and FA values increase steadily across adolescence, with boys exhibiting an overall steeper incline in volume compared to girls (Perrin et al, 2009), and these typical sex differences relating, in part, to gonadal hormone levels (Herting et al, 2012). Among typically developing individuals, positive associations are also observed between cognitive function and FA (Tamnes et al, 2010; Lee et al, 2017). Human DTI studies of adolescents with FASD have previously reported alterations in WM microstructure compared to controls, including regionally specific reduced FA and increased MD values (reviewed in (Wozniak and Muetzel, 2011)).…”
Section: Introductionmentioning
confidence: 99%